Bifunctional Catalysts Containing Zn(II) and Imidazolium Salt Ionic Liquids for Chemical Fixation of Carbon Dioxide. Issue 3 (28th December 2020) - Shang, Hui; Bai, Shiyang; Yao, Jie; Ma, Shuangshuang; Sun, Jihong; Su, Hongjing; Wu, Xia
Abstract: Zn(II) can efficiently promote the catalytic performance of imidazolium salt ionic liquids (imi‐ILs) for the chemical fixation of CO2 into epoxides. To obtain sustainability, immobilized bifunctional catalysts containing both imi‐ILs and Zn(II) were prepared using bimodal mesoporous silica (BMMs) as carrier, through grafting of Zn(OAc)2 and 1‐(trimethoxysilyl)propyl‐3‐methylimidazolium chloride (Si‐imi) separately in the nanopores. The catalysts, named as BMMs−Zn&ILs, were identified as efficient catalysts for cycloaddition reaction of CO2 into epoxides under solvent‐free conditions. BMMs−Zn&ILs showed good catalytic activity, which increased with the increase of the molar ratio of Zn(II) to Si‐imi. As a comparison, different catalytic systems including homogeneous imi‐IL, BMMs‐ILs and BMMs−Zn were studied to demonstrate different cooperation behaviors. Furthermore, the kinetics studies of homogeneous and heterogeneous bifunctional catalysts were employed to confirm the differences, as well as to support the proposed cooperative catalysis mechanism in the nanopores. Abstract : A series of immobilized bifunctional catalyst containing Zn and imidazolium salt ionic liquids for chemical fixation of carbon dioxide into cyclic carbonate were designed and fabricated. The synthesized bifunctional catalysts all present much higher activities than the signal site catalysts and even the homogeneous catalysts.